The Works of the late Reverend Mr. Robert Ricaltoun ... - Riccaltoun, Robert (Printed by A. Murray & J. Cochran, for the author's son; sold by J. Dickson, 1771)
v. 1. Essays on human nature, and essays on several of the doctrines of revelation.- v. 2. A treatise on the general plan of revelation; and the Christian life, or Dissertation on Galatians ii, 20.- v. 3. Notes and observations on the Epistle to the Galatians.